2012
DOI: 10.1371/journal.pntd.0001664
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Induction of Paromomycin Resistance in Antimony-Resistant Strains of L. donovani: Outcome Dependent on In Vitro Selection Protocol

Abstract: Paromomycin (PMM) has recently been introduced for treatment of visceral leishmaniasis in India. Although no clinical resistance has yet been reported, proactive vigilance should be warranted. The present in vitro study compared the outcome and stability of experimental PMM-resistance induction on promastigotes and intracellular amastigotes. Cloned antimony-resistant L. donovani field isolates from India and Nepal were exposed to stepwise increasing concentrations of PMM (up to 500 µM), either as promastigotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 26 publications
(33 reference statements)
1
72
0
1
Order By: Relevance
“…Since the first MIL-resistant isolate was reported in 2012, a second naturally resistant strain was found by our research group (3, 4). As for PMM resistance, this was already reported to develop fairly readily (4,7,9,20). Moreover, numerous in vitro studies demonstrated quick selection of MIL and PMM resistance on promastigotes (6)(7)(8).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Since the first MIL-resistant isolate was reported in 2012, a second naturally resistant strain was found by our research group (3, 4). As for PMM resistance, this was already reported to develop fairly readily (4,7,9,20). Moreover, numerous in vitro studies demonstrated quick selection of MIL and PMM resistance on promastigotes (6)(7)(8).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, numerous in vitro studies demonstrated quick selection of MIL and PMM resistance on promastigotes (6)(7)(8). To target the more relevant amastigote stage in mammalian infection, our research group previously developed an in vitro resistance selection protocol on intracellular amastigotes (9). For PMM, several strains with PMM-resistant amastigotes but still fully PMMsusceptible promastigotes were obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited studies on PMM resistance in Leishmania, which evince the involvement of mitochondrial membrane potential and decreases in drug uptake (14)(15)(16). In our previous report, we compared the outcomes and stability of experimental PMM resistance induction in promastigotes and intracellular amastigotes (17). Here, we exploited laboratory-generated PMM-resistant (PMM-R) parasites to examine changes in membrane fluidity, drug accumulation, mutations in rRNA genes, and mRNA expression of ATP-binding cassette (ABC) transporter genes (MDR1 and MRPA) and protein phosphatase 2A (PP2A).…”
mentioning
confidence: 99%
“…Elle est actuellement en phase III des essais cliniques réalisés en Afrique de l'Est. Cependant, des études de laboratoire ont montré que ces deux molécules pouvaient sélectionner rapidement des parasites résistants [24][25][26][27], ce qui repré-sente un risque lors de traitements, même de courtes durées. Pour la miltéfosine, sa disponibilité sur le marché des médicaments de comptoir et son utilisation incontrôlée peuvent grandement augmenter ce risque de développement de résistances.…”
Section: Leishmaniose Cutanéeunclassified